Study on the application of wireless communication technology in digital communities in Guangdong - วรพงศ์พัชร์ ณฐาพัชร์; Thavisin, Natthanon; Viphoouparakhot, Boonyanuch (วิทยาการบริหารภาครัฐสมัยใหม่, 2024)
In recent years, the integration of wireless communication technology has significantly influenced the evolution of digital communities. This study investigates the meaning, types, and characteristics of wireless communication technologies, explores their applications within digital communities, and identifies associated challenges and potential solutions. We employed a qualitative research methodology, concentrating on a rural district in Guangdong Province. We collected data through in-depth interviews and focus group discussions involving community members, local leaders, and technology experts. A semi-structured interview guide, reviewed by information technology specialists, ensured content validity. We applied thematic analysis to extract key themes and insights from the data. The findings reveal that wireless communication technologies, such as 5G and Bluetooth, are instrumental in enhancing connectivity and operational efficiency within digital communities. However, data security and privacy concerns remain significant obstacles. The study also underscores the importance of community engagement in implementing wireless technologies, highlighting the need for training and awareness programs. This research emphasizes the pivotal role of wireless communication technologies in shaping digital communities while addressing the necessity of robust security measures. We urge stakeholders to prioritize community involvement and education in order to maximize the benefits of these technologies. Future research should examine the long-term impacts of wireless technologies on social cohesion and evaluate the effectiveness of security protocols in safeguarding community data.